Implementasi Strategi Pembelajaran Kooperatif dalam Mengembangkan Keterampilan Kolaborasi Siswa dalam Pembelajaran di SD/MI - Yubi Yubi; Muhammad Ta’rifudin; Oman Farhurohman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to analyze the implementation of cooperative learning strategies in developing students' collaboration skills in learning in SD/MI based on a literature review. Cooperative learning is considered relevant because learning requires students to work together in groups to find solutions to problems given to them. The method used in this research is a literature study, where researchers collect and analyze various literature sources related to contextual learning and its application in learning. These sources include books, scientific journals, and previous research that supports contextual learning theory and practice. The results of this literature review show that cooperative learning strategies can increase student involvement and student collaboration skills in learning. Thus, this strategy can encourage student involvement in group activities and collaboration, forming a learning environment that supports the development of various crucial skills.